An improved protection-free one-pot chemical synthesis of purine locked nucleic acid nucleoside-5′-triphosphates. (1st December 2021) - Shanmugasundaram, Muthian; Senthilvelan, Annamalai; Kore, Anilkumar R.
Abstract: A simple, reliable, straightforward, and efficient method for the gram-scale chemical synthesis of purine locked nucleic acid (LNA) nucleotides such as LNA-guanosine-5′-triphosphate (LNA-GTP) and LNA-adenosine-5′-triphosphate (LNA-ATP) starting from the corresponding nucleoside is described. The overall reaction utilizes an improved "one-pot, three-step" Ludwig synthetic strategy that involves the monophosphorylation of LNA nucleoside, followed by the reaction with tributylammonium pyrophosphate and subsequent hydrolysis of the resulting cyclic intermediate using water to furnish the corresponding purine LNA nucleotide in good yield with high purity (>99.5%).